Pioneering of mocaf flour business in Tempursari village, Candimulyo, Magelang regency - Retno Rusdjijati; Muhammad Rajif Ghany; Ari Sativanto; Rezqi Maulana Akhsan; Zhawung Dio Saputra; Rozi Rahmansyah Riyan Purfita (Community Empowerment, 2022)
One of the business activities being initiated by the Women Farmers Group (KWT) in Tempursari Village, Candimulyo District, Magelang Regency is the production of mocaf flour. Mocaf stands for modified cassava flour which is flour made from cassava. This business was initiated, considering that cassava production in Tempursari Village is abundant and only sold fresh at low prices, so that it can increase the selling value. In order to start this business, KWT has been assisted by 2 units of production machines in the form of a pulverizing machine and a flour machine and have also been trained in the process of making mocaf flour. However, this business has not been developed seriously, KWT members are more focused on the various chips business that was initiated previous year. In order to motivate KWT members to immediately develop a mocaf flour business, we employ the mentoring activities as a real action. The result of PPMT activity is the engineering of the grater tool with the addition of a knife, assistancing in making mocaf flour, designing packaging and logos, and helping product promotion through social media.